Analisis Sistem Rantai Pasok PT. Semen Padang - Fitri Julasmasari; Hendra Saputra; Mury Wijaya; Opie Analia; Rahmad Illahi (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2011)
Supply Chain Management is a concept or mechanism to increase the total productivity of companiesin the supply chain through optimization of the time, location and quantity of material flow from rawmaterials into semi-finished products and finished products. Supply Chain Management is not onlyabout the relationship with the supplier but also the link between the company and consumers. Tofind out the value of the company supply chain performance within a certain time, we need a draftmodel of supply chain performance measurement in which the design will be implemented at thecompany. By knowing the value of supply kunerja chainnya the company can improve theeffectiveness and productivity of the organization to achieve organizational goals is to win thecompetition, and increase corporate profits.